KAJIAN EVALUASI IMPLEMENTASI KURIKULUM DI DAERAH - Baedhowi1 Baedhowi1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2005)
Curriculum is believed as one of essential components in the education field thatsignificantly affects the learning process and results. A good curriculum will be ableto help society to fulfill their needs and to anticipate the facing challenges. Thus, anystudy on the curriculum implementation seems relevant to the recent condition ofeducation field in Indonesia that has been adapting a new school curriculum since the beginning of district autonomy era. This will expectedly result on the availability of curriculum to be the guideline or reference for â€œ...learning environment, teachingmethods, the resources provided for learning, the systems of assessment, the school ethos and the ways in which students and staff behave towards one anotherâ€(Australian Curriculum Council, 1985). Such a study that has been recently carriedout by the Expert Staff of National Education Minister for Curriculum Developmentand Education Media in 9 provinces in Indonesia. Beforehand, the curriculum hasbeen tried out in 3 other provinces, alternately the Central Java, Bali, and SouthSumatra provinces.